IMPLEMENTASI ASSOSIATION MINING MENGGUNAKAN ALGORITMA DEKOMPOSISI UNTUK MENGETAHUI POLA TREN, SIKLIK DAN FAKTOR MUSIMAN PADA PERPUSTAKAAN DAERAH KABUPATEN SUKABUMI - Sinta Kusumawardhani (Jurnal RESTIKOM : Riset Teknik Informatika dan Komputer, 2019)
The library consists of the term librarius which means about books, which consists of a room that is part of a building (building) or a building that contains collection books that are arranged and arranged thus, easy to find and use according to time-needs required by the reader is an information center where library materials are collected, processed, stored and maintained for later dissemination so that it can be utilized to the maximum extent possible by library users. Prediction of the number of visitors at the Regional Library of Sukabumi District increased in March while in December the number of visitors decreased.